2022
DOI: 10.3390/su14073968
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Plant Species Response and Performance for Green Belt Development: Implications for Semi-Urban Ecosystem Restoration

Abstract: Screened plant species with potential for green belt development can act as eco-sustainable tools for restoring the polluted ecosystem. Eight plant species from two study locations in Ado-Odo, Ota, Ogun State, Nigeria, were examined to identify their air pollution response and performance by deploying two air pollution indices, namely air pollution tolerance index (APTI) and anticipated performance index (API). APTI results identified all screened plants as sensitive species suitable as bio-indicators of air p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 80 publications
4
4
0
Order By: Relevance
“…Although, it was also observed that as air pollution rises, cell permeability increases and causes a significant loss of minerals and water from the plant cell and can lead to early senescence of leaves (Ogunkunle et al 2015 ). Similar conformities in results were previously assessed by Bharti et al ( 2018 ), Rai ( 2019 ), Anake et al ( 2022 ), and Goswami et al ( 2022 ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Although, it was also observed that as air pollution rises, cell permeability increases and causes a significant loss of minerals and water from the plant cell and can lead to early senescence of leaves (Ogunkunle et al 2015 ). Similar conformities in results were previously assessed by Bharti et al ( 2018 ), Rai ( 2019 ), Anake et al ( 2022 ), and Goswami et al ( 2022 ).…”
Section: Resultssupporting
confidence: 91%
“…Increased level of air pollution adversely affects the concentration of chlorophyll, carotenoids, and AA in a plant cell (Rai 2019 ). Similar conformity in results was shown in studies by Anake et al ( 2022 ); Goswami et al ( 2022 ); Mandal and Dhal ( 2022 ) that identified a reduction in total chlorophyll content in the polluted area in comparison to nonpolluted sites.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…According to the plant survival rate and plant growth index, it was confirmed that the dominant plants were more adaptable to the polluted substrate [14]. Another study screened out plants suitable for ecosystem restoration by comparing the tolerance and performance indices of plants to further promote ecological restoration [15]. In addition, some researchers have linked the above two aspects to study the plant-soil feedback mechanism [16], the relationship between microbial communities, and soil physicochemical properties [17,18] to study the dynamic cycle process of mine ecological restoration from a more comprehensive perspective.…”
Section: Introductionmentioning
confidence: 99%